Unlocking global opportunities: Exploring bilingual teaching in Spanish business law - González Jiménez, Pedro Mario (Docencia y Derecho, 2023)
This paper explores the complexities of bilingual teaching in Spanish business law, highlighting both opportunities and challenges. Teaching in English offers global recognition and collaboration, especially in areas like international trade. However, nuances in Spanish commercial law and subjects rooted in national legal traditions, like insolvency law, pose hurdles. Anisomorphism between legal systems complicates direct translations, emphasizing the need for a strategic approach. Despite harmonization through directives, elements shaped by national legislation persist. Scarcity of English teaching materials necessitates ad hoc preparation, impacting educators and student independence. A judicious approach to bilingual teaching is crucial, balancing global benefits with linguistic intricacies and resource challenges.